Effect of Emotional Intelligence on Job Satisfaction among nurses: descriptive study - Ayyazada Farhana, Samina Kouser, Mansoor Ghani, Tahira Khatoon, Rozina Asghar, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Emotional intelligence affects a nurse's capacity for critical thought, the use of evidence and information in practise, as well as other areas of nursing. Aim: To ascertain the relationship between nurses' job happiness and emotional intelligence in a few tertiary care facilities. Study design: A descriptive Correlational study. Methodology: Structured self-administered questionnaires are used to gather data. The participants' socio-demographic data was presented in the first section. The surveys used to assess the nurses' job satisfaction contained 21 items. The second section of the questionnaire included a self-evaluation of emotional intelligence and management skills for several emotional variations (awareness, relationship, and management). Data is analyzed by SPSS version-20. Results: 79.2% of subjects had high emotional intelligence. According to Job Satisfaction Levels, the majority of respondents (95.11%) were happy with their jobs. The relationship between emotional intelligence and job satisfaction is statistically significant, with an r-value of 0.240 and a P-value of 0.008 respectively. It demonstrates how people with high emotional intelligence typically exhibit more positive behaviors. Practical Implication: This study aided in the investigation of the link between nurses' job happiness and emotional intelligence. Conclusion: The findings emphasise the importance of using emotional intelligence and familiarity with emotions, such as (recognising, understanding, managing, and controlling emotions), to boost nurse job satisfaction, which in turn enhances the quality of nursing care. When employing nursing staff, management should make emotional intelligence a top requirement. Keywords: Job Satisfaction, Emotional Intelligence, Nursing profession and Evaluation.